Diagnostic Tests for Helicobacter pylori Infection - Tonny Loho (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2008)
Helicobacter pylori is a spiral-shaped Gram negative bacterium, has 4-6 flagella, live in microaerophillic condition, has urease, oxidase and catalase enzymes. Helicobacter pylori (H. pylori) infection                                       is etiologically involved in dyspepsia, gastric ulcer, duodenal ulcer, gastric adenocarcinoma and primary gastric B-cell lymphoma. Transmissions of H. pylori is by fecal-oral and oral-oral.4 Diagnostic tests for H. pylori infection can be divided into 2 categories, invasive and non invasive methods. Invasive methods to diagnose H. pylori infection are performed by endoscopy and biopsy. Gastric biopsies are then tested with culture, histologic assessment, urease test and PCR test. Non-invasive methods to diagnose H. pylori infections consist of urea breath test (UBT), 15NH + excretion test, serologic detection of IgG and IgA in the blood, fecal antigen detection and fecal PCR detection. All these tests have its own advantages and limitations. But non-invasive tests have several advantages compared to invasive tests as cheaper, more convenient and easier to perform. To apply these tests accurately, it is very important to understand the principle of the test, how to perform the test, the sensitivity, specificity, positive predictive value, negative predictive value and to recognize all the sources of error which can happen with each test and accurate interpretation. Keywords: Helicobacter pylori infection, diagnostic tests, invasive methods, non-invasive methods